2010
DOI: 10.3324/haematol.2009.014704
|View full text |Cite
|
Sign up to set email alerts
|

High-dose RHAMM-R3 peptide vaccination for patients with acute myeloid leukemia, myelodysplastic syndrome and multiple myeloma

Abstract: BackgroundRecently, we demonstrated immunological and clinical responses to a RHAMM-R3 peptide vaccine in patients with acute myeloid leukemia, myelodysplastic syndrome and multiple myeloma. To improve the outcome of the vaccine, a second cohort was vaccinated with a higher dose of 1,000 μg peptide. Design and MethodsNine patients received four vaccinations subcutaneously at a biweekly interval. Immunomonitoring of cytotoxic CD8+ as well as regulatory CD4 + T cells was performed by flow cytometry as well as by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
98
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 22 publications
7
98
0
Order By: Relevance
“…Furthermore, the presence of these immune responses was associated with better clinical outcome in AML; 6 v) finally, RHAMM-derived peptide vaccination resulted in potent immune responses that were linked with a clinical benefit, while a negative impact on normal HSC function was not reported. 7,8 Together these observations support the hypothesis that RHAMM/HMMR may be suitable for AML, by fulfilling several parameters that have been identified as important in the selection of candidate antigens for immunotherapy for cancer. 9 Nevertheless, two further considerations are equally important.…”
supporting
confidence: 69%
“…Furthermore, the presence of these immune responses was associated with better clinical outcome in AML; 6 v) finally, RHAMM-derived peptide vaccination resulted in potent immune responses that were linked with a clinical benefit, while a negative impact on normal HSC function was not reported. 7,8 Together these observations support the hypothesis that RHAMM/HMMR may be suitable for AML, by fulfilling several parameters that have been identified as important in the selection of candidate antigens for immunotherapy for cancer. 9 Nevertheless, two further considerations are equally important.…”
supporting
confidence: 69%
“…Majeti et al 29 compared the gene expression signature of LSCs with that of normal HSCs and identified over 3000 genes with dysregulated expression in LSCs. 29 The published data set also includes several genes encoding proteins that can be recognized by the immune system and act as LAAs, such as Elicited (T) 47,95 Natural (B/T) 25 …”
Section: Criterion 2: Frequency and Pattern Of Expressionmentioning
confidence: 99%
“…47 A second trial of high-dose RHAMM 165-173 vaccination in nine patients with diverse myeloid malignancies failed to show any clinical benefit in the sole AML patient who was included; three other patients, two with myelodysplastic syndromes and one with myeloma, had variable clinical responses. 95 The potential use of hTERT in active specific immunotherapy for AML is currently under investigation. 96 Preliminary data from a phase I/II clinical trial of hTERT-loaded dendritic cell vaccination in AML patients have suggested an improvement in disease-free survival at 12 months, particularly among patients with a high risk of relapse.…”
Section: Criterion 5: Clinical Relevancementioning
confidence: 99%
“…CD8 -antigen presenting cells (APCs) were irradiated with 30 Gy and pulsed for 2 h with either a TAA-derived peptide or a control peptide at a concentration of 20 µg/ml. For all peptides, as well as for the control peptides, the same conditions and reagents were used as previously described (27).…”
Section: Mixed Lymphocyte Peptide Culture (Mlpc)mentioning
confidence: 99%
“…After 8 days of MLPC culture, the T2-cell line pulsed with peptide was used as APCs in the ELISpot. IFNγ and GrB ELISpot assays were performed as previously described (22,27). Fig.…”
Section: Mixed Lymphocyte Peptide Culture (Mlpc)mentioning
confidence: 99%